Alkali Silica Reaction in concrete: the Argentinian experience - Milanesi, Carlos Alberto (2018)
Argentina is an extended country where a large variety of aggregates is available even in the same region. More than 100 examples of structures, placed in regions with different climates, damaged by ASR have been reported since 1950. Many tests on mortar or concrete involving different temperatures, alkali contents, and sample volumes have been studied in order to find the most suitable conditions for the evaluation of reactive aggregates. This paper summarizes the present knowledge and design criteria adopted in Argentina in order to avoid or mitigate ASR in concrete.